Memperoleh keterampilan dalam bola basket melalui pembelajaran observasional - D. Panganiban, Teejay; H. San Miguel, Michael (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
With the ongoing COVID-19 pandemic requiring us to practice social or physical distancing, the concept of observational learning has become particularly relevant. This learning process involves observing others, retaining the information, and replicating the observed behaviors later. This research determined the skill acquisition in Basketball through observational learning of pre-service teachers at Batangas State University JPLPC-Malvar to determine its implications for teaching physical education. It specifically addressed the respondents' profile in terms of sex, program, GWA, and socio-economic status significant relationship between the respondents' profile and their skill acquisition in Basketball through observational learning. This descriptive-correlational study was conducted to assess the 89 students enrolled in the College of Teacher Education program at the Batangas State University JPLPC-Malvar campus. An adequate number of respondents and an appropriate sampling technique are adopted to produce a valid and reliable result. Using a self-made questionnaire and appropriate statistical measures, the results revealed that the respondents are greatly female, mostly from Bachelor of Secondary Education, belong to the Superior Group, and have a middle income. Chi-Square revealed that sex, program, GWA, and socio-economic status have significant relationships when correlated to their encountered challenges. The above-mentioned findings recommend using multimedia or video demonstrating skills in physical education classes to train the students' skills and strengthen the use of observational learning and conducting a webinar that focuses on how we can learn Basketball through observational learning.